Uso y destino de las remesas recibidas por los moradores del sector de Solanda y su aplicación práctica en un proyecto de factibilidad, caso: Restaurante Light Bar - Gaibor Len, Paola Fernanda (2012)
The Light Bar Co. Restaurant. Ltda. Was devoted to the preparation and marketing of light food, this being understood as a balanced diet with adequate food groups different amounts. Demand was considered certain variable # people who consume foods like daily: lunch, special dishes, salads and desserts in restaurants Solanda third category in the southern suburb of the city of Quito. Accordingly, the offer was established based on # jobs offered in the segment of the third category of restaurants located in the southern suburb of Solanda Quito.